Tunable Rectification in 2D Porphyrinic Metal–Organic Framework Nanosheets Molecular Heterojunctions - Bing Huang; Xiaoyu Wang; Chaoguang He; Yongkang Zhang; Pan Qi; Ying Wang; Tong Li; Huixia Fu; Hui Wei; Cunlan Guo (Advanced Electronic Materials)
Abstract As functional electrical devices advance, new strategies for regulating electrical properties are essential for achieving diverse electrical performance. In this study, molecular heterojunction rectifiers are constructed by connecting porphyrinic 2D metal–organic framework (2D MOF) nanosheets and oligophenylene thiols self‐assembled monolayers (OPT SAMs) within metal electrodes. The rectification characteristics can be tuned by the molecular length of OPT and the coordinated metal atom in the center of 2D MOFs. Specifically, a rectification ratio of more than 1.67 orders of magnitude is achieved in the heterojunction composed of 2D Zn‐TCPP MOF nanosheet (TCCP, tetrakis(4‐carboxyphenyl) porphyrin) and OPT3 SAM. Combining Kelvin probe force microscopy measurements and first‐principles calculations of the 2D MOF nanosheets, it elucidates that the rectification variations come from the adjustment of energy level alignment at OPT SAMs//2D MOF interface, leading to asymmetric charge transport with the voltage polarities. This strategy can be further extended to Cu‐MOF nanosheets, which also exhibit rectification behaviors when placed on OPT2 SAMs. This work provides a universal and flexible strategy for regulating the electrical behaviors of MOFs without the need for specific design and synthesis, paving the way for the development of MOF‐based functional electronic devices.